Genetic etiological analysis of auditory neuropathy spectrum disorder by next-generation sequencing - Sun, Lianhua; Lin, Zhengyu; Zhang, Jifang; Shen, Jiali; Wang, Xiaowen; Yang, Jun (Frontiers in Neurology, 2022)
Objective Auditory neuropathy spectrum disease (ANSD) is caused by both environmental and genetic causes and is defined by a failure in peripheral auditory neural transmission but normal outer hair cells function. To date, 13 genes identified as potentially causing ANSD have been documented. To study the etiology of ANSD, we collected 9 probands with ANSD diagnosed in the clinic and performed targeted next-generation sequencing. Methods Nine probands have been identified as ANSD based on the results of the ABR tests and DPOAE/CMs. Genomic DNA extracted from their peripheral blood was examined by next-generation sequencing (NGS) for a gene panel to identify any potential causal variations. For candidate pathogenic genes, we performed co-segregation among all family members of the pedigrees. Subsequently, using a mini-gene assay, we examined the function of a novel splice site mutant of OTOF. Results We analyzed nine cases of patients with ANSD with normal CMs/DPOAE and abnormal ABR, discovered three novel mutants of the OTOF gene that are known to cause ANSD, and six cases of other gene mutations including TBC1D24, LARS2, TIMM8A, MITF, and WFS1. Conclusion Our results extend the mutation spectrum of the OTOF gene and indicate that the genetic etiology of ANSD may be related to gene mutations of TBC1D24, LARS2, TIMM8A, MITF, and WFS1.